Memperkuat ’Urf dalam Pengembangan Hukum Islam - Ach Maimun (Faculty of Sharia IAIN Madura collaboration with The Islamic Law Researcher Association (APHI), 2017)
Sejauh ini, keberadaan ’urf sebagai sumber hukum Islam tidak menonjol. Padahal `urf memiliki posisi penting untuk pengembangan Islam di Nusantara yang kaya budaya. `Urf dapat menjadi pembendung kolompok yang anti terhadap tradisi lokal. Para ulama sejatinya telah berbicara panjang lebar tentang ’urf sebagai dasar hukum. Para mujtahid dan mufti disyaratkan menguasai tradisi suatu masyarakat dan cermat mempertimbangkannya. Untuk itu diperlukan upaya penguatan ‘urf dalam rangka pengembangan hukum Islam agar dapat tetap berperan di masa depan. Tujuan itu dapat dilakukan dengan beberapa langkah, yaitu memperbaiki cara memahami dan mendudukkan nash sebagai landasan utama hukum Islam, menegaskan posisi fiqih sebagai hasil ijtihad manusiawi yang historis dan kultural, dan melakukan negosiasi antara doktrin Islam dengan tradisi sekaligus menciptakan tradisi baru sebagai wujud penerjemahan doktrin yang bersifat mutlak. (The existence of 'urf as one of sources of Islamic law is not dominant while it has an important position in the context of Islamic development in Indonesia, which is rich of culture and tradition. `Urf can be a barrier against those who are anti-local traditions. Actually, Islamic scholars have discussed a lot about ‘urf as the legal basis in the context of Islamic law. Mujtahid (experts in islamic law) and mufti (advisers on religious law) are required to be knowledgable of the traditions of a society and carefully consider them.Therefore, it is necessary to strengthen the 'urf for developing Islamic law in order to keep it playing a role in the future. In so doing, it is necessary to take several steps; improving the way to understand and place the texts of the Quran as the main foundation of Islamic law, affirming the position of Islamic jurisprudence as the result of historical and cultural human interpretation and judgement (ijtihad), and negotiating between Islamic doctrine and tradition while creating new traditions as a form of absolute doctrinal translation.